Covid 19 Pandemic Challenges: The Youth Unemployment In Nigeria - Adebimpe, Oyewobi Ifeoluwapo; Adetunji, Adeniyi Temitope; Nwachukwu, Chijioke; Hieu, Vu Minh (The journal of contemporary issues in business and government, 2021)
When it comes to employment sector, there is an urgent need for wider investigations about the impact of COVID-19 on unemployment to explore possible damages to existing patterns of youth employability, and the alignment of government policy with institutional needs. This study is aimed to assess the short-term challenges of COVID-19 pandemic on the youth unemployment crisis in Nigeria. For this study, data from National Bureau of Statistics (NBS) study and other published data from literature have been analyzed to determine the challenges of COVID-19 pandemic on youth unemployment in Nigeria. From the analysis carried out, the effect of COVID-19 pandemic on unemployment via difference-in-difference assessment shows that the Nigeria’s unemployment rate ranked 30.1 percent in the fourth quarter of 2020. The study reveals that the unemployment rate among young people that is, ages 15-34years is 30.1%, up from 26.7%. The study also finds that 64% of the considerably increased inflows from employment into unemployment were due to the COVID-19 shutdown measures. It has been also established in the study that as at the fourth quarter of 2020, youth unemployment rate rose to 1% indicating that about 22,764,614 million Nigerian youths remain unemployed. The study concludes that, in sum, the shutdown measures amplified increased unemployment in. The study recommended the participation of private companies amongst others, by creating jobs in averting the challenges of COVID-19 pandemic on increased youth unemployment in the country.